2021
DOI: 10.21608/svuijm.2021.64583.1100
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Red Blood cell Distribution Width and Extent of Coronary Artery Disease in Patient with ST Elevation Myocardial Infarction

Abstract: Background: Coronary Artery Disease (CAD) is the leading cause of morbidity and mortality all around the world. Red cell distribution width (RDW) is an indicator for the variability and size of circulating erythrocytes, has recently been shown to be an independent predictor of prognosis in patients with cardiovascular disease. Objectives: to assess the relationship between RDW and severity of coronary artery disease (CAD) by SYNTAX score in patients with ST-elevation myocardial infarction (STEMI) undergoing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…16 Another study demonstrated a similar positive correlation (r=0.464 p<0.001) between RDW and the severity of CAD (measured by SYNTAX score). 14 Another study reported a statistical correlation between RDW values and coronary artery calcium scoring (r=0.53; p<0.001). 17 All these results, including the present study, indicated that RDW is a marker for CAD.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…16 Another study demonstrated a similar positive correlation (r=0.464 p<0.001) between RDW and the severity of CAD (measured by SYNTAX score). 14 Another study reported a statistical correlation between RDW values and coronary artery calcium scoring (r=0.53; p<0.001). 17 All these results, including the present study, indicated that RDW is a marker for CAD.…”
Section: Discussionmentioning
confidence: 95%
“…The mean age of the current study population was similar to another study, but the age was earlier than in the developed countries. [12][13][14] CAG is the gold standard for the clinical judgment of CAD, and the Gensini score is a quantitative indicator for estimating coronary artery stenosis based on CAG. Gensini score is a widely used angiographic scoring system for quantifying the severity of CAD.…”
Section: Discussionmentioning
confidence: 99%